2013
DOI: 10.1177/1420326x13504316
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modelling of the effect of fresh air rate on dynamic variation of CO2 in the waiting room of a railway station

Abstract: This paper reports the investigation of the relationship between CO 2 concentration and passenger quantity in the waiting room of a railway station. In situ survey was conducted to collect data on purchased passenger tickets, train schedule and arrival times at Changsha railway station and to establish modelling results. The predictive model is based on the established passenger flow pattern and dynamic governing equations of CO 2 concentration as a reference indicator of indoor air quality (IAQ) in the waitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…38 The initial condition parameters of the model were set according to a simulation model of Changsha South Railway Station and related literature as shown in Table 2. 39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The initial condition parameters of the model were set according to a simulation model of Changsha South Railway Station and related literature as shown in Table 2. 39…”
Section: Resultsmentioning
confidence: 99%
“…38 The initial condition parameters of the model were set according to a simulation model of Changsha South Railway Station and related literature as shown in Table 2. 39 In order to verify the validity of the model, we used the field meteorological data of Changsha on 7, 8, 10 and 11 September 2013 as input term to start simulation. Then we verified the result by 48 groups of hourly (8:00-19:00) indoor dry bulb temperature values and work surface (0.85 m) illuminance values which were measured in the elevated waiting room of Changsha South Station on 7, 8, 10 and 11 September 2013.…”
Section: The Establishment and Verification Of Calculation Modelmentioning
confidence: 99%
“…The literature has many examples of studies in which CO 2 concentration in different classrooms is measured to carry out different analyses, such as determining the times of the day in which the pollutant exceeds an upper limit [15], evaluating the improvement of ventilation and compliance with regulations by keeping doors and/or windows open or closed [16,17], studying the effects of natural ventilation [18] or mechanically-controlled ventilation systems [19] on CO 2 levels, calculating the air exchange rate [20,21], and determining the ventilation rate [20]. Other research in which CO 2 concentrations are also studied include an analysis carried out in naturally-ventilated office buildings in two Italian cities considering different opening and closing configurations for doors and windows [22], a study on air-conditioned laboratories in a Malaysian university with different numbers of occupants [23], a study focused on a waiting room in a Chinese railway station [24], and another one centered on a typical small apartment in Korea [25]. Recently, Di Gilio et al [26] studied CO 2 concentrations in Italian classrooms and found that the levels of this pollutant can be used as an indicator of SARS-CoV-2 transmission risk.…”
Section: Introductionmentioning
confidence: 99%
“…Ventilation could effectively supply fresh air to indoors. 10 Among several ventilation patterns, natural ventilation is an environmental and economical method to improve indoor environment because it need not consume energy. Therefore, determining how to design effective natural ventilation and investigating the unsteady flow of particle dispersion and deposition in a workshop with a ferroalloy furnace during tapping is very important.…”
Section: Introductionmentioning
confidence: 99%